2013
DOI: 10.2478/s11658-013-0095-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammasomes and their regulators in prostate cancer initiation, progression and metastasis

Abstract: Prostate cancer is one of the main cancers that affect men, especially older men. Though there has been considerable progress in understanding the progression of prostate cancer, the drivers of its development need to be studied more comprehensively. The emergence of resistant forms has also increased the clinical challenges involved in the treatment of prostate cancer. Recent evidence has suggested that inflammation might play an important role at various stages of cancer development. This review focuses on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
2
26
1
Order By: Relevance
“…As adaptive immune cells, analysis of two major prostate tumor-infiltrating lymphocyte subsets showed that capsular and perineural invasion as well as biochemical progression was related to strong infiltration of T and B lymphocytes [15, 19]. Mc Ardle et al [20] showed that the presence of increase CD4+ T-lymphocyte infiltrate was associated with poor PC prognosis and it can predict survival.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As adaptive immune cells, analysis of two major prostate tumor-infiltrating lymphocyte subsets showed that capsular and perineural invasion as well as biochemical progression was related to strong infiltration of T and B lymphocytes [15, 19]. Mc Ardle et al [20] showed that the presence of increase CD4+ T-lymphocyte infiltrate was associated with poor PC prognosis and it can predict survival.…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of B-lymphocytes in cancer has been overshadowed by the interest in T-cell responses, B-cells can play a complementary role in the immune response against tumor [15]. Gannon et al [23] compared metastatic and non-metastatic pelvic lymph nodes from PC cases and controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Decades of histological observations have led to the recognition of inflammatory and immune mediators as active participants in the pathogenesis, surveillance, and progression of prostate cancer [17][18][19][20][21] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%